Relationship Between Self-Repair and Structural Complexity of Vocal Expressions: Exploring the Relationship Between Self-Repair and Syntactic Complexity in Second Language English Learners (Journal of Advances and Scholarly Researches in Allied Education, 2011)
This study is concerned with the investigation ofthe relationship between the type of self-repair and thestructural complexity of Vocalexpressions in which theyappear, focusing mainly on syntactic self-repairs. Thesubjects of the studywere 48 students, learning English as a secondlanguage in Delhi. Specifically,this study hassought to establish a relationship between the occurrence of  syntactic repairs and  the complexity  of  syntactic structures  L2 speakers  use. Thefindings suggest that the occurrence ofrepairs in general (that is, without relating specific categories of repair to structural complexity) does not appear to be related to the syntactic complexity of thestructures in which they occur. However, the scrutinyof the position of syntactic self-repairs isindicative of a relationship between the frequencyof syntactic self-repairs and the complexityof the syntactic structures, suggesting that for thosewho learn English astheir second language, thecomplexity of syntactic structures must be one, if not the, contributingfactor leading to the occurrenceof syntactic repairs. For otherkinds of repairs, including phonological,morphological/lexical, appropriacyand information-structuring repairs, the occurrence of repairs is unrelated to syntactic complexity.